An Integrated Geomorphological Framework for Preliminary Coastal Hazard Assessment in the Resource Conflict Zone of Bangka Regency, Indonesia - Taufik Budi Waskita; Bachtiar Wahyu Mutaqin; Muh Aris Marfai; Dinda Prayunita (JPG (Jurnal Pendidikan Geografi), 2026)
Coastal environments in tropical archipelagic regions are increasingly exposed to the combined pressures of hydrodynamic forcing and anthropogenic modification, yet spatially explicit hazard assessments remain limited, particularly in data-constrained contexts. This study develops and applies a geomorphology-based framework for preliminary coastal hazard assessment in Bangka Regency, Indonesia, focusing on extreme waves and coastal erosion. The results reveal pervasive hazard conditions across the 73.60 km² coastal zone, with no areas classified as low hazard. Moderate (40.08 km²) and high hazard (33.52 km²) classes dominate, indicating system-wide exposure. Hazard distribution is strongly controlled by geomorphological configuration, with unconsolidated coastal systems such as beach ridges and estuarine plains exhibiting the highest hazard intensities, while intertidal wetlands provide partial mitigation through wave attenuation and sediment stabilization. Parameter analysis identifies wave height as the primary driver of hazard, while land use change and shoreline modification significantly amplify hazard through disruption of sediment dynamics and reduction of natural resilience. The findings demonstrate that coastal hazard in Bangka Regency emerges from the interaction of physical processes and human activities, rather than natural forcing alone. The proposed framework provides a practical and transferable tool for generating spatially explicit hazard information in data-scarce environments. This preliminary assessment establishes a baseline for more comprehensive risk analysis and supports the need for integrated, evidence-based coastal management strategies.